Wykorzystanie mierników Sharpe'a i Treynora do oceny efektywności inwestycyjnej OFE - Frasyniuk-Pietrzyk, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Total return of pension funds published by the Polish Finlciak Supervision Authority is a controversial issue. Total return of a fund is an incomplete measure of the performance because it ignores risk. The paper presents the most popular measures of modern portfolio theory - the Sharpe and Treynor ratio. This paper analyzes the statistical significance of these measures. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 99-109